Purification and separation of sunflower-seed oil in the traveling electric field - Назаренко, Игорь Петрович (Eastern-European Journal of Enterprise Technologies, 2014)
The results of experimental studies on the purification and separation of sunflower-seed oil in the traveling electric field were presented. Studies were conducted on a pilot plant, which is the processing unit and power supply. In processing unit, there is a multilayered system of cylindrical electrodes, creating the traveling electric field. The possibility of the purification process of sunflower-seed oil from nonoleaginous impurities and phosphatides and separation of these fractions in the traveling electric field was shown. Technological parameters of the process: time; voltage and frequency of the electric field that allow to obtain the purification rate of oil from nonoleaginous impurities of 98 %, and from the hydrated phosphatides – 75 % were justified. During the separation of these fractions, the separation factor of nonoleaginous impurities reaches 90 % and phosphatides – 68 %.